Implementation of Problem Based Learning to Improve Students' Mathematics Learning Outcomes at UPT SMP Negeri 10 Tapung - Nurmila Sari; Armis Armis; Putri Yuanita (Global READ Center, 2025)
The success of students in learning mathematics cannot be separated from the mathematics learning process at school. In the learning process at school, improving learning outcomes is very necessary in order to obtain complete learning outcomes. Therefore, teachers must be able to apply learning models that can create a learning atmosphere that attracts students' attention, can train students' way of thinking to understand mathematical concepts and can play an active role in the learning process. So, teachers need to apply the Problem Based Learning (PBL) model to improve student activity and student learning outcomes. PBL helps students gather information, build new knowledge, and develop the skills needed for active and independent learning. The purpose of the study was to improve student learning outcomes. Data were collected through observation, tests, and documentation. Based on the results of the research that the researcher has conducted, it can be concluded that the application of the PBL model can improve the learning process and can improve the mathematics learning outcomes of class VIIIC students of UPT SMP Negeri 10 Tapung in the even semester of the 2024/2025 academic year on the material of the Two Variable Linear Equation System.